Agamemnon - Hall, Peter; Harrison, Toni; Aeschylus (The Oresteia trilogy/ Aeschlus, 1983)
The play opera as the watchman at King Agamemnon's palace sees the beacon that announces the fall of Troy, The chorus of old tell the background to the story Trohan War. When Agamemnon returns home after a 10 year absence, his given Clythenmestra welcomes him but Cassandra (daugther of the vanguised Trojan King Siam and now Agamemnon's captive mistress) foretells his murder. The murder of Agamemnon will be a double revenge.